2,517 UMP students return to hometowns to celebrate Aidilfitri - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 7 May 2021 - A total of 2,517 Universiti Malaysia Pahang (UMP) students will return to their hometowns in stages to celebrate Hari Raya Aidilfitri.